Immunoprotective Effect of Cocos nucifera Oil on Sheep Red Blood Cell-Induced Immunocompromised Rats - MacDonald Idu; Igori Debby; Benjamin Ogunma Gabriel (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
The aim of this study is to investigate the immunoprotective effects of cold-pressed coconut oil in immunocompromised rat. Standard procedure was used to perform this research work with a modified method. The effect of immunomodulatory properties of coconut oil was evaluated after challenging the animals with 0.3 ml sheep red blood cells (SRBCs) intraperitoneally and further treated with graded doses (0.25, 0.5 and 1.0 ml/kg i.p) of the oil extract for 21 days. The hematological, CD4, CD8 biochemical and histopathological analysis were evaluated. Result obtained from this study showed a significant increase in hematological indexes (WBC: 11.70; LYM: 9.9 GRAN: 8.0 and HGB: 15.57) across the treated groups, but majorly at lowest dose (0.25 ml/kg). More so a significant increase in CD4 and CD8 Count specifically at 0.25 ml/kg (7.763 and 7.830). Anti-oxidant property of the oil extract at 0.25 ml/kg had a significant reduction in malondialdehyde with an increased in antioxidant enzymes (SOD, CAT and GPx) when compared with untreated control. The body weight of the animals in the treated groups showed a significant increase at 0.25 ml/kg of the oil extract when compared with the untreated control. Liver function test (ALT, AST and ALP) showed no significant increase in the treatment groups when compared with the controls. The histopathological result reveals a normal physiological structure of the heart, lungs, spleen, liver and kidney in lowest dose of the oil extract. In conclusion, this study validated the ethnomedicinal property of the plant.